Pupils with sensory disabilities in physical education classes: Attitudes and preferences - Petra Kurková; Dagmar Nemček; Jela Labudová (Palacký University Olomouc, 2015)
Background: The key factor that affects the success of shaping positive attitudes towards regular life-long performance of physical activity (PA) is the pupils' level of inner motivation. This is influenced, among other things, by their family background, the educational institution that they attend and the educator's competencies. Objective: The purpose of this study was to describe and analyse the attitudes among pupils with sensory disabilities in physical education (PE) classes. A partial objective was to compare the preferences for various PA by pupils with sensory disabilities in PE classes. Method: A non-standardized questionnaire was used to collect the data. The sample was based on the following features: a) a participant had to be deaf or hard of hearing, b) a participant had to have a visual disability, and c) had to have been educated in special educational settings. The data were quantified on the percentage basis. To carry out cross-group statistical testing of differences, a ratio analysis with the help of the Chi-square test was applied. The level of statistical significance was set to p < .05. We analysed the data of 70 pupils attending the second stage of two elementary schools in Slovakia: a) 37 pupils (22 boys and 15 girls, age 13.3 ± 1.45 years) from a school for the deaf, and b) 33 pupils (14 boys and 19 girls, age 13.4 ± 1.41 years) from a school for the blind. Results: The differences in the preferences for various PA during PE classes in the cross-group comparison of pupils with sensory disabilities were discovered. A comparison of the opinions of pupils with sensory disabilities pointed out a difference consisting in a higher percentage of positive attitudes among pupils with visual disabilities in indicators of popularity, importance, the pupils' efforts and feelings towards education. A statistically significant difference was discovered only in feelings during PE classes. This result may be considered proof of the suitability of the educational environment for pupils with visual disabilities. Conclusion: Comparing the opinions of pupils with sensory disabilities showed a difference in that pupils with visual disability have a higher percentage of positive views in all studied indicators: popularity, importance, pupils' efforts and their feelings towards PE.